ANALISIS POSTUR KERJA DENGAN METODE WERA SERTA PERANCANGAN ALAT BANTU IKAT PINGGANG DAN KURSI UNTUK KEGIATAN MENCUCI MOBIL MANUAL - Tanuwijaya, Dharmawan; Widodo, Lamto; Andres (Universitas Tarumanagara, 2023)
This research is located in conventional car washes where there are still many who use human labor in carrying out car wash activities. The posture during the car wash is considered less ergonomic, so this study aims to help car wash workers reduce their fatigue and even help their work position become more ergonomic. This research began with observations at the car wash and also interviews with workers. Interviews with the workers were conducted using the Nordic Body Map (NBM). Based on the results of observations and interviews, it was determined that the working posture was considered less ergonomic where there were three working postures, namely the posture when taking the water hose, the posture of washing the side of the car, and the posture of washing the top of the car. The three postures that are considered problematic are analyzed using the Workplace Ergonomic Risk Assessment (WERA) to determine the value of their ergonomics. When he learned that the three postures were problematic, the research continued by designing tools to reduce workload, this design was carried out using the VDI 2222 method. Designing with the VDI 2222 method there are 4 stages, namely analysis, concept, design, and completion. By using the VDI 2222 method, the concept, size, and specifications needed for belts and seats are known as a car washing aid. The last stage of this study is to re-analyze with the WERA method on all three postures but with the help of tools.